ANALYSIS OF THE EFFECT OF QUICK RATIO (QR), DEBT TO EQUITY RATIO (DER) AND RETURN ON EQUITY (ROE) ON STOCK PRICES IN FOOD AND BEVERAGE (F&B) COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) PERIOD (2021 - 2022) - Octaviani, Anggi; Aisyiyah, Ellya; Daningrum, Etika; Tamim , Sephana Fhita Roza; Damayanti, Dila (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2023)
This study aims to examine the effect of the activity ratio (Quick Ratio), solvency ratio (Debt to Equity Ratio), and profitability ratio (Return On Equity) on stock prices in the good consumer sector listed on the Indonesian Stock Exchange (IDX) for the period 2021 - 2022. The population in this study were 36 food and beverage companies listed on the Indonesia Stock Exchange (IDX). The samples in this study were 27 companies with purposive random sampling. This research is a quantitative type using data analysis techniques is classical assumption test analysis techniques, multiple linear regression and the coefficient of determination. The results of this study are as follows: (1) Quick Ratio (QR) has no significant effect on stock prices in food and beverage companies listed on the Indonesia Stock Exchange for the period 2021 - 2022. (2) Debt to Equity Ratio (DER) has a significant effect on stock prices for food and beverage companies listed on the Indonesia Stock Exchange for the 2021 - 2022 period. (3) Return On Equity (ROE) has a significant effect on stock prices for food and beverage companies listed on the Indonesia Stock Exchange for the 2021 - 2022 period. (4) Quick Ratio (QR), Debt to Equity Ratio (DER), Return On Equity (ROE) have a positive simultaneous effect on stock prices listed on the Indonesia Stock Exchange for the 2021-2022 period.